Circuito T - Arias-Flores, Jacqueline Tatiana (Instituto Tecnológico de Costa Rica., 2019)
The capital of Costa Rica, San José, has been experiencing a constant process of urban transformation, where living places have been replaced by new commercial ones, and as a consequence the population’s migration to the periphery of the city, unchain a series of urban problems that have affected the habitability of the city. As part of the strategies for the recovering of San José’s downtown neighborhoods, in 2015 the Municipality of San José and the Program of Strengthening the Urban Territory from the Technological Institute of Costa Rica have developed a plan called: “Plan of Action Plan for the Historical Center of San José” (Plan CHSJ). They propose eight important axes of action for the improvement of the four principal districts of the central capital city, which are going to incorporate in this investigation. Throughout the research and proposal results, the current topic about the recovery of central urban areas will be addressed, and will be incorporated according to the needs of the cultural entrepreneurship from the study zone. The project for recovering the civic, economic, recreational and cultural life located in La Soledad and González Lahmann neighborhood’s, belonging to the Cathedral district from San José’s canton. Moreover, as part of urban recovery strategies, the new Transit-Oriented Urban Development Model , internationally known as TOD, will be applied because of the privileged location of the study zone, between two of the principal Railway Stations of the Urban Train that cross four provincial headers in the Metropolitan Area. The CIRCUIT T: A Proposal of Urban Recuperation, takes up current theories for the recovering urban areas, which are in deterioration, and involves the cultural factor as principal strategy of urban design. The proposal contributes with the objectives of the Plan CHSJ, and will be an extension of the Project about the urban recuperation of 30 blocks of the Historic Center of San José.
propuesta de recuperación urbana como parte de la extensión de "Proyecto 30 manzanas" del Centro Histórico de San José
Proyecto de graduación (Licenciatura en Arquitectura y Urbanismo) Instituto Tecnológico de Costa Rica, Escuela de Arquitectura y Urbanismo, 2019.
Keywords: San José (Costa Rica); Recuperación urbana; Centros históricos -- Diseño arquitectónico; Urbanismo; Planeamiento urbano